O discurso da obsolescência: o velho, o novo e o consumismo - Almeida, João Flávio de (Universidade Federal de São Carlos, 2013)
This work aims to analyze the media statements about the "new": analyzing the discourse that older objects and knowledge that are not yet unusable. To do so, we will try to tread a path through the theoretical issue of consumption (before becoming consumerism), trying to analyze historically the conversion process of enduring relationships (with objects, people, knowledge etc.) in ephemeral relationships, from discourse of obsolescence. Once defined and analyzed the theoretical framework, we will analyze three discursive materiality (in order: the movie "The Last Laugh", the advertising campaign "Intel Ultrabook Convertible", and the movie "The Devil Wears Prada") with the intention of analyzing the discourse about the "new" and obsolescence.
The discourse of obsolescence: the old, the new and consumerism
Keywords: Análise do discurso; Sociedade de consumo; Obsolescência; Pós-modernidade; Pêcheux, Michel, 1938-1983; Sartre, Jean-Paul, 1905-1980; Cinema; Consumismo; Modernidade líquida; Novo; Novidade; Discourse analysis; Consumption; Consumerism; Liquid Modernity; Postmodernity; New; Novelty; Obsolescence; CIENCIAS SOCIAIS APLICADAS